Analysis of seed production and seed shattering in a new artificial grassland forage: pigeon pea - Li, Xinyong; Sheng, Wei; Dong, Qianzhen; Huang, Rui; Dong, Rongshu; Liu, Guodao; Ding, Xipeng; Zhang, Jingwen (Frontiers in Plant Science, 2023)
Pigeon pea is a perennial leguminous plant that is widely cultivated as a forage and pharmaceutical plant in subtropical and tropical areas, especially in artificial grasslands. Higher seed shattering is one of the most important factors in potentially increasing the seed yield of pigeon pea. Advance technology is necessary to increase the seed yield of pigeon pea. Through 2 consecutive years of field observations, we found that fertile tiller number was the key component of the seed yield of pigeon pea. Multiplex morphology, histology, and cytological and hydrolytic enzyme activity analysis showed that shatter-susceptible and shatter-resistant pigeon peas possessed an abscission layer at the same time; however, abscission layer cells dissolved earlier in shattering-susceptible pigeon pea, which led to the tearing of the abscission layer. The number of vascular bundle cells and vascular bundle area were the most significant negative factors affecting seed shattering. Cellulase and polygalacturonase were involved in the dehiscence process. In addition, we inferred that larger vascular bundle tissues and cells in the ventral suture of seed pods could effectively resist the dehiscence pressure of the abscission layer. This study provides foundation for further molecular studies to increase the seed yield of pigeon pea.